Students’ Self-Regulated Learning on Division Algorithm with a Fair-Share Method - Murdiyati, Efa; Herman, Tatang (Universitas Pendidikan Indonesia, 2024)
Learning environments should be where constructive and self-regulated learning is fostered. Teachers should transform their mathematics classes into something more challenging and fun while building students’ numeracy skills and learning character. Self-regulated learning is a learning character that students must have to become agentic life-long learners in an unpredictable, dynamic, and ever-changing society. This study aimed to describe students’ self-regulated learning on the division algorithm with a fair-share method. This was descriptive qualitative research using the case study method conducted in six weeks. The subjects of this study are ten students in grade four. The data sources were collected from self-regulated learning scales and students’ learning activity observation sheets. The data was analyzed through data reduction, data presentation, and conclusion. This study unveiled that a teaching division algorithm with a fair-share method could nourish students’ self-regulated learning. Proven that only 20% of students had moderate levels of self-regulated learning; 50% of students had high levels of self-regulated learning; and 30% of students had very high levels of self-regulated learning. Furthermore, the average score of self-regulated dimensions was classified as very good. The fair-share method also impacted students’ behavior to be excited in learning and exposing them to mathematical modeling through the dividing candies activity.